2014
DOI: 10.1016/j.bmc.2013.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-analogous peptidyl phosphorus esters as mechanism-based inhibitors of γ-glutamyl transpeptidase for probing cysteinyl-glycine binding site

Abstract: γ-Glutamyl transpeptidase (GGT) catalyzing the cleavage of γ-glutamyl bond of glutathione and its S-conjugates is involved in a number of physiological and pathological processes through glutathione homeostasis. Defining its Cys-Gly binding site is extremely important not only in defining the physiological function of GGT, but also in designing specific and effective inhibitors for pharmaceutical purposes. Here we report the synthesis and evaluation of a series of glutathione-analogous peptidyl phosphorus este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…As shown in Scheme 1 , the cyano group on the pyrazole ring was first hydrolyzed into a reactive carboxyl group [ 23 ], which enables easy chemical modification. Followed by condensation reactions with amino acid esters in the presence of EDC∙HCl and DMAP [ 24 , 25 ], 12 amino acid ester–fipronil conjugates ( 3a – l ) were obtained. Hydrolysis of the methyl ester group in 3a – l with lithium hydroxide [ 10 , 26 ] provided the new amino acid–fipronil conjugates 4a – l in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1 , the cyano group on the pyrazole ring was first hydrolyzed into a reactive carboxyl group [ 23 ], which enables easy chemical modification. Followed by condensation reactions with amino acid esters in the presence of EDC∙HCl and DMAP [ 24 , 25 ], 12 amino acid ester–fipronil conjugates ( 3a – l ) were obtained. Hydrolysis of the methyl ester group in 3a – l with lithium hydroxide [ 10 , 26 ] provided the new amino acid–fipronil conjugates 4a – l in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…A series of GSH analogous peptidyl phosphorus esters, which are mechanism- based inhibitors of human GGT and EcGGT, were synthesized to evaluate the structural and stereochemical preferences of the Cys-Gly binding site of GGTs. 55) Both enzymes were inhibited strongly and irreversibly by these inhibitors with phenoxide as a good leaving group. It was found that human GGT was highly selective for L-aliphatic amino acid such as L-2-aminobutyrate (L-Cys mimic) at the Cys binding site, whereas EcGGT significantly preferred L-Phe mimic at this site.…”
Section: Identification Of the Catalytic Nucleophile Of Ecggtmentioning
confidence: 99%
“…On the other hand, EcGGT was not selective for GSH, but still retained the dipeptide binding site. 55) d) The reaction mechanism of EcGGT deduced from the structure of .-glutamyl-enzyme intermediate.…”
Section: Identification Of the Catalytic Nucleophile Of Ecggtmentioning
confidence: 99%
“…The reaction was stirred for 10 minutes and then cooled to -78 ˚C at which point a solution of 2-butynoic acid (0.50 g, 5.8 mmol) in THF (12 mL) was added and the reaction was stirred at -78 ˚C for 10 minutes and then warmed to -5 ˚C and stirred for 45 minutes. The reaction was poured into cooled (0 ˚C) 1 M HCl (100 mL) and extracted with EtOAc (3 x 30 mL), the combined organic layers were washed with brine (20 mL), dried (MgSO4), filtered, concentrated and purified by chromatography on SiO2 (10% EtOAc:hexanes) to yield 860 mg (81%) of S6 as a colorless oil: 1 N-Methoxy-N,3-dimethyldec-2-enamide (S7). (E)-3-methyldec-2-enoic acid (S6) (120 mg, 0.66 mmol) was dissolved in THF (2.1 mL) and 2-chloro-4,6-dimethoxy-1,3,5-triazine (140 mg, 0.79 mmol) was added followed by the addition of N-methylmorpholine (0.22 mL, 2.0 mmol).…”
Section: General Procedures For the Preparation Of O-tbs-α-hydroxy Amimentioning
confidence: 99%
“…The reaction was then poured into saturated sodium bicarbonate and extracted with ethyl acetate. The combined organic layers were washed with brine, dried over magnesium sulfate, filtered, concentrated in vacuo, and purified by chromatography on SiO2 (20% EtOAc:hexanes) to yield 61.2 mg (73%) of 16 as a colorless oil: Rf = 0.55 (20% EtOAc:hexanes); 1…”
Section: General Procedures For the Preparation Of O-tbs-α-hydroxy Amimentioning
confidence: 99%